Peer advocacy and access to healthcare for people who are homeless in London, UK: a mixed method impact, economic and process evaluation protocol. Issue 6 (17th June 2021) - Rathod, Sujit D; Guise, Andrew; Annand, PJ; Hosseini, Paniz; Williamson, Elizabeth; Miners, Alec; Bowgett, Kate; Burrows, Martin; Aldridge, Robert W; Luchenski, Serena; Menezes, Dee; Story, Alistair; et al.
Abstract : Introduction: People who are homeless experience higher morbidity and mortality than the general population. These outcomes are exacerbated by inequitable access to healthcare. Emerging evidence suggests a role for peer advocates—that is, trained volunteers with lived experience—to support people who are homeless to access healthcare. Methods and analysis: We plan to conduct a mixed methods evaluation to assess the effects (qualitative, cohort and economic studies); processes and contexts (qualitative study); fidelity; and acceptability and reach (process study) of Peer Advocacy on people who are homeless and on peers themselves in London, UK. People with lived experience of homelessness are partners in the design, execution, analysis and dissemination of the evaluation. Ethics and dissemination: Ethics approval for all study designs has been granted by the National Health Service London—Dulwich Research Ethics Committee (UK) and the London School of Hygiene and Tropical Medicine's Ethics Committee (UK). We plan to disseminate study progress and outputs via a website, conference presentations, community meetings and peer-reviewed journal articles.